(untitled) (Innovaciones Educativas, 2023)
This systematization aims to bring to light the teaching experience using actual data in problem-solving for the students to develop skills related to literacy and statistical thinking. One aspect to consider for the design of this didactic strategy was the COVID-19 pandemic context because all courses were to be taught 100% in a virtual modality. The didactic experience begins with the application of an online questionnaire addressed to the students of introductory Statistics courses. These courses are part of the many study programs offered at Universidad de Costa Rica. From the data collected online and data published by the Ministry of Health related to the COVID virus, various learning guides were generated focused on the basic concepts of descriptive statistics. Among the main results is the importance of technological mediation to achieve literacy and statistical thinking, focusing on aspects related to data quality, its summarization, and interpretation. Additionally, the students managed to go beyond statistical calculation since they established substantive conclusions related to their discipline.